2020
DOI: 10.3390/microorganisms8020187
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Inorganic and Organic Nitrogen Sources by Dinophysis acuminata and D. acuta

Abstract: Dinoflagellate species of Dinophysis are obligate mixotrophs that require light, nutrients, and prey for sustained growth. Information about their nitrogenous nutrient preferences and their uptake kinetics are scarce. This study aimed to determine the preferred nitrogen sources in cultures of D. acuminata and D. acuta strains from the Galician Rías Baixas (NW Spain) and to compare their uptake kinetics. Well-fed versus starved cultures of D. acuminata and D. acuta were supplied with N15 labeled inorganic (nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…These preferences were confirmed in laboratory experiments (Hattenrath-Lehmann and Gobler 2015). García-Portela et al (2020) showed that neither D. acuminata nor D. acuta take up nitrate. A review of transcriptomic databases showed a paucity of nitrate transporter homologs in D. acuminata.…”
Section: Light and Nutritional Sources For Dinophysis Speciesmentioning
confidence: 64%
See 1 more Smart Citation
“…These preferences were confirmed in laboratory experiments (Hattenrath-Lehmann and Gobler 2015). García-Portela et al (2020) showed that neither D. acuminata nor D. acuta take up nitrate. A review of transcriptomic databases showed a paucity of nitrate transporter homologs in D. acuminata.…”
Section: Light and Nutritional Sources For Dinophysis Speciesmentioning
confidence: 64%
“…These observation suggested that the two species have different physiological and behavioural adaptations. Laboratory culture studies confirmed the different responses of the two species to light intensity and quality (García-Portela et al, 2018;Kim et al, 2008), turbulence (García-Portela et al, 2019) and nitrogen sources (García-Portela et al, 2020;Hattenrath-Lehmann and Gobler, 2015).…”
Section: Introductionmentioning
confidence: 63%
“…All the plankton functional types could uptake NH 4 + . All except Dinophysis could also use NO 3 − as this genus seems unable to use this N-source García-Portela et al, 2020). However, the construct of the Dinophysis model is based on the generic construct of a pSNCM (Anschütz and Flynn, 2020) and, therefore, should evidence of Dinopysis using NO 3 − become available, then the model can be readily modified to enable NO 3 − uptake for Dinophysis just as it is enabled for the other pSNCM, Mesodinium.…”
Section: Model Structurementioning
confidence: 99%
“…Since the successful mixotrophic culture of D. acuminata by Park et al in 2006, several laboratory studies have been carried out on Dinophysis about the effects of (1) abiotic factors, such as nutrient availability, concentration and uptake (e.g. Nagai et al, 2008, García-Portela et al, 2020, temperature (e.g. Basti et al, 2018, Kamiyama et al, 2010, salinity (Fiorendino et al, 2020), light intensity and quality (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Smith et al, 2018), prey concentration (e.g. Kim et al, 2008, Smith et al, 2018 and prey exudates (Gao et al, 2019;Nagai et al, 2011), nutritional status (García-Portela et al, 2020) or (3) geographical origin (Fux et al, 2011) on the physiology and/or toxicity. Nevertheless, laboratory studies exploring the short-term effect of salinity stress on physiology and metabolites production (including toxins) are still lacking.…”
Section: Introductionmentioning
confidence: 99%